The effect of creative applicable methods on attracting the audience towards urban commercial advertisements from 2000 to 2020. (15th September 2020) - Rasoolipour, Somayeh; Emamiifar, Seyyed Nezameddin
The present study attempts to investigate the criteria of creativity in the process of designing urban advertisements. The main purpose of the current research was to study the creativity in commercial advertising and its features to convey the message to the audience effectively. This study falls in the category of descriptive-analytical studies. Data collection carried out using library research and statistical society included samples from commercial advertisements throughout the world from 2000 to 2020. The results of the study show that in addition to persuading audience, environmental factors (particularly light and space) have been most often used to the same degree in commercial advertising. Based on the findings of the present study, those methods are successful by which advertisements work with the least and most limited possibilities in order to offer the best creative ideas in applying ads on attracting the audience and gaining abundant profits and returns. To be sure, this requires recognising the behaviour of audience and customers (audience-recognition), that is, before any kind of action, potential evaluations and investigations must be done upon society and public opinion.